2017
DOI: 10.31234/osf.io/wtygs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How to create a human communication system: A theoretical model

Abstract: Following a synthesis of naturalistic and experimental studies of language creation, we propose a theoretical model that describes the process through which human communication systems might arise and evolve. Three key processes are proposed that give rise to effective, efficient and shared human communication systems: 1) motivated signs that directly resemble their meaning facilitate cognitive alignment, improving communication success; 2) behavioral alignment onto an inventory of shared sign-to-meaning mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…One possibility is that adults have a better insight into the pragmatic requirement that interlocutors need to be able to map signals onto meanings, which is likely to drive what Lister & Fay (2017) termed the creation of 'motivated signs'.…”
Section: The Nature Of Children's Limitations In Creating and Transmimentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that adults have a better insight into the pragmatic requirement that interlocutors need to be able to map signals onto meanings, which is likely to drive what Lister & Fay (2017) termed the creation of 'motivated signs'.…”
Section: The Nature Of Children's Limitations In Creating and Transmimentioning
confidence: 99%
“…Finally, children may be less adept at aligning their own signals with those of their interlocutor, as our findings suggest. Lister & Fay (2017) propose that behavioural alignment drives cognitive alignment such that when interlocutors copy signals produced by their communication partners this will gradually lead to the establishment of shared cognitive representations. However, behavioural alignment requires monitoring of the match between one's own and the interlocutor's productions, to compute an error term in cases of mismatch, and to adjust subsequent productions to minimise this error term.…”
Section: The Nature Of Children's Limitations In Creating and Transmimentioning
confidence: 99%
“…This gives rise to a tension between sign innovation and alignment. One way to resolve this tension is through the production of iconic signs, which share a direct resemblance to their referent and so can be understood without prior knowledge (Lister & Fay, 2017). Another way to resolve this tension is through the creation of enculturated signs – signs that are mutually intelligible to members of the same linguistic community because of their shared cultural knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Language use is a joint activity that occurs between people, the goal of which is cognitive alignment (e.g. Fusaroli, Rączaszek-Leonardi & Tylén, 2014; Clark & Wilkes-Gibbs, 1986; Garrod & Pickering, 2004; 2009, Lister & Fay, 2017). Cognitive alignment is enabled by behaviour alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Referential communication studies in which participants were asked to memorize or negotiate a set of novel signals showed that for some signaling systems, e.g. drawings or gestures, absolute iconicity can emerge right from the start (Fay et al, 2014a,b;Motamedi et al, 2019), and the iconic signals subsequently become simplified and conventionalized with repeated use (Lister & Fay, 2017). For other signaling systems like Leap Motion (Little et al, 2017) or binary tone sequences (Kempe et al, 2019), where physical resemblance between signal and meaning space is limited, emergence of relative iconicity requires transmission over several generations as it takes time for users to find suitable and well-motivated mappings between signal features and relevant meaning dimensions, e.g.…”
Section: Combinatorial and Compositional Structurementioning
confidence: 99%